The Relations between the Family Nutrition and Physical Activity Levels and Prevalence of Obesity of Their Children in Turkey - Ece, Cuma (Progress in Nutrition, 2021)
Study objectives: The aim of the study is to examine the relationship between diet and physical activity levels of family with their children's the prevalence of obesity. Method: A total of 433 parents, including mothers (n = 217) and fathers (n = 216), participated in the study. Data form containing socio-demographic characteristics and family nutrition and physical activity (FNPA) questionnaire were applied to the participants. FNPA was developed by Ihmels et al. (2009) and adapted into Turkish by Özdemir (2020). Descriptive statistics and independent samples t test, One-way ANOVA and Pearson correlation analysis were used in the analysis of the data obtained. Results: As a result of the research, no relationship was found between mother, father and child Body Mass Index (BMI) values and total scores of FNPA scale (p> 0.05). It has been determined that the area where the families live has no effect on their nutrition and physical activity levels. It was found that families with high income levels had higher nutritional and physical activity levels than families with low and middle-income levels (p